Auditory Spatial Recalibration in Congenital Blind Individuals - Finocchietti, Sara; Cappagli, Giulia; Gori, Monica (Frontiers in Neuroscience, 2017)
Blind individuals show impairments for auditory spatial skills that require complex spatial representation of the environment. We suggest that this is partially due to the egocentric frame of reference used by blind individuals. Here we investigate the possibility of reducing the mentioned auditory spatial impairments with an audio-motor training. Our hypothesis is that the association between a motor command and the corresponding movement’s sensory feedback can provide an allocentric frame of reference and consequently help blind individuals in understanding complex spatial relationships. Subjects were required to localize the end point of a moving sound before and after either 2-minutes of audio-motor training or a complete rest. During the training, subjects were asked to move their hand, and consequently the sound source, to freely explore the space around the setup and the body. Both congenital blind (N=20) and blindfolded healthy controls (N=28) participated in the study. Results suggest that the audio-motor training was effective in improving space perception of blind individuals. The improvement was not observed in those subjects that did not perform the training. This study demonstrates that it is possible to recalibrate the auditory spatial representation in congenital blind individuals with a short audio-motor training and provides new insights for rehabilitation protocols in blind people.